Longitudinal associations of body mass index, waist circumference, and waist-to-Hip ratio with biomarkers of oxidative stress in older adults: results of a large cohort study - Anusruti, Ankita; Jansen, Eugène H. J. M.; Gao, Xin; Xuan, Yang; Brenner, Hermann; Schöttker, Ben (Obesity facts, 2020)
Background: In the literature, obesity is discussed as a determinant of high oxidative stress (OS). Hence, prevention or reduction of obesity could prevent high OS and subsequently serve as a target for “healthy aging.” Methods: Diacron’s reactive oxygen metabolites test (D-ROM) and total thiol levels (TTL), a marker of antioxidant defense capacity, were measured in 1,734 participants of a population-based cohort study of older adults (age range: 57-83 years) at 2 time points 3 years apart. The longitudinal associations of body mass index, waist-to-hip ratio, and waist circumference with D-ROM and TTL were assessed with multivariable adjusted generalized linear models. Dose-response analyses were conducted with restricted cubic splines. Results: D-ROM was not significantly associated with any of the weight measures. On the contrary, TTL showed statistically significant, inverse linear associations with all weight measures. Conclusion: A healthy body weight seems to be highly relevant for the antioxidative defense capacity of human beings. In contrast, D-ROM levels were independent of the study participant’s weight. Clinical trials are needed to corroborate if loss of weight by obese individuals can effectively increase TTL and subsequently also life expectancy.
Gesehen am 09.04.2020